Connecting the complex microstructure of LDPE to its rheology and processing properties via a combined fractionation and modelling approach. Issue 52 (7th October 2021) - Zentel, Kristina Maria; Eselem Bungu, Paul Severin; Degenkolb, Jonas; Pasch, Harald; Busch, Markus
Abstract : The complex microstructure of LDPE regarding branching and molecular weight was correlated to its rheology and processing properties via preparative fractionation and modelling. Abstract : Well-defined mini-plant low density polyethylene samples were fractionated preparatively according to their crystallizability via preparative temperature rising elution fractionation and according to molecular weight via preparative solvent gradient fractionation (pSGF). Rheology of the fractions was measured in both the small amplitude oscillatory shear (SAOS) and the non-linear extension regimes. The linear and non-linear rheology of the pTREF fractions were dominated by molecular weight effects, while the impact of the higher degree of long chain branching for the pSGF fractions with higher molecular weights was observed in van Gurp–Palmen plots and in strain hardening behavior in the extensional rheology measurements. Additionally, the experimental fractionation process was mimicked via modelling. The branching topologies of the bulk samples were obtained by coupled kinetic and Monte Carlo calculations. These topologies were fractionated computationally and the result were used to predict the rheological behavior of the individual fractions by applying the BoB algorithm with no parameter adjustment. The experimental observed trends were predicted by the model and the overall agreement was acceptable. This study demonstrates, that polymer fractionation is possible on a preparative scale and allows for the polymer flow properties characterization of the individual fractions, a method that is highly relevant during processing. Moreover, the fractionation process is followed and understood from the modelling point of view.